Air pollution is associated with depressive symptoms in elderly women with cognitive impairment. (March 2020) - Altuğ, Hicran; Fuks, Kateryna B.; Hüls, Anke; Mayer, Anne-Kathrin; Tham, Rachel; Krutmann, Jean; Schikowski, Tamara
Highlights: Depression and cognitive impairment are comorbid conditions. We assessed associations between air pollution and diagnosis/symptoms of depression. Air pollution was associated with both diagnosis and symptoms of depression. Cognition modified the association between air pollution and depressive symptoms. Lower cognition may pose greater risk for air pollution related depressive symptoms. Abstract: Background: Studies on air pollution and depression in the elderly are limited and the results are heterogeneous. Objectives: We examined the association of ambient air pollution exposure and diagnosis and symptoms of depression in the elderly; and whether any associations were confounded or modified by cognitive decline. Methods: We enrolled 821 elderly women from the German SALIA cohort (follow-up examination, 2007–2010). Self-reported depressive symptoms and level of cognition were evaluated using the CESD-R Scale and the CERAD-Plus test, respectively. We used two depression endpoints for analyses: self-reported doctor diagnosis of depression and frequency of depressive symptoms (CESD-R score). Long-term concentrations of particulate matter (PM) size fractions and nitrogen oxides (NO x ) modeled by land-use regression were assigned to home addresses. Cross-sectional associations were assessed using adjusted logistic and linear regression models. Results: Concentrations of coarse particles (PMcoarse ), fine particles (PM2.5 and PM2.5 abs ) and NO2 were significantly associated with diagnosis of depression (e.g. for PM2.5 OR = 1.62, 95%CI: 1.06, 2.46 and for NO2 OR = 1.54, 95% CI: 1.08, 2.19). Similarly, an increase of one interquartile range in PM10, PM2.5, NO2 and NOx was associated with depressive symptoms assessed with the CESD-R score (e.g. for PM2.5 16.2% difference in the mean; 95% CI: 5.8%, 26.5% and for NO2 14.5%; 95% CI: 4.8%, 24.2%). These associations were stronger in women with cognitive decline (e.g. Pint for PM2.5 :0.022 and NO2 :0.017) compared to women with normal cognition. In addition, living less than 100 m distance to major roads was significantly associated with diagnosis (OR = 1.99, 95% CI: 1.14, 3.47) and symptoms (19.7%; 95% CI: 4.3%, 35.1%) of depression. We did not observe any interaction effect of cognition on prior diagnosis of depression. Conclusions: Exposure to air pollution was associated with diagnosis of depression and depressive symptoms in elderly women. Women with impaired cognition may be at greater risk of depressive symptoms when exposed to air pollution.